MOTIF KETERTARIKAN PEMBACA: - Vilya Lakstian Catra Mulia (Jurnal Dialog, 2017)
Reading activity which is supported by the rich reading materials has shown its positive influence in the development of civilized society today. Besides being a part of religious orders, reading is an attempt to acquire and strengthen knowledge as well as to gain new experience. The reading content reflects the needs and objectives of the readers. Now, the relationship between the authors and the readers should met. The integrity of reading content is built by the organization of main ideas and supporting ideas, making it easier for readers to analyze patterns of structured, phased, and logical orders. The idea organization in a reading text stimulates the brain to evaluate and control over what it reads. Therefore, it needs what is known as metacognition in order to create the critical literacy for our community as the text readers. We certainly expect that reading is to construct our community to be more intelligent and insightful through the ideas presented, without getting slipped on undesirable mission of the authors.